Effects of Different Soil Amendments on Soil Chemical Characteristics and Sugar Beet Growth in Soda Salinized Cultivated Land - Tian Lu; Guo Xiaoxia; Su Wenbin; Huang Chunyan; Li Zhi; Jian Caiyuan; Han Kang; Xue Chunlei (Shuitu baochi tongbao)
[Objective] The suitable soil amendments applied to soda saline alkali cultivated land in the Xiliaohe Plain of Inner Mongolia were screened in order to provide a theoretical basis for the comprehensive development and utilization of saline alkali land and the sustainable development of agriculture in this area. [Methods] Three soil amendments (i.e., organic silicon fertilizer, humic acid fertilizer, and microbial fertilizer) were selected to analyze their effects on soil pH value, alkalinity, total salt content, organic matter content, sugar beet growth, yield, and quality of soda salinized cultivated land. [Results] ① The three soil amendments improved the soil chemical properties of soda salinized cultivated land to varying degrees. Specifically, they effectively reduced soil pH value, alkalinity, and total salt content, and increased organic matter content. Soil pH value, alkalinity, total salt content, and organic matter content of different treatments in the 10—20 cm soil layer were greater than that in the 0—10 cm soil layer. Compared with the control, the reduction range of soil pH value and alkalinity, and increase range of organic matter content of the three soil amendments in 10—20 cm soil layer were greater than in the 0—10 cm soil layer, while the reduction range of soil total salt content in the 0—10 cm soil layer was greater than in the 10—20 cm layer. Among the three soil amendments, organic silicon fertilizer had the greatest effect on increasing soil pH value, alkalinity, total salt content, and organic matter content. ② Compared with the control, the three soil amendments significantly increased emergence rate and survival rate of sugar beet, and increased growth indexes such as plant height, leaf area index, and whole plant fresh weight of sugar beet, thereby improving sugar beet yield and quality, and the organic silicon fertilizer showed the best effects. The three soil amendments increased the output value of sugar beet, but the economic benefit of only organic silicon fertilizer was higher than that of the control. ③ The main factors affecting the emergence, survival, growth, yield, and quality of sugar beet in soda saline alkali cultivated land were soil pH value, alkalinity, total salt content, and organic matter content. The application of soil amendments can directly regulate soil chemical characteristics, thereby effectively ensuring sugar beet growth and development, and increasing yield and quality. [Conclusion] From the comprehensive consideration of soil characteristics, sugar beet growth, yield, quality, and economic benefits, the organic silicon fertilizer was more effective in improving of soda saline alkali cultivated land and sugar beet cultivation compared with the other two soil amendments.